Diffusion wear mechanism during high-speed machining of 7475-T7351 aluminum alloy with carbide end mills - Calatoru, V.D.; Balazinski, M.; Mayer, J.R.R.; Paris, H.; L’Espérance, G. (Wear, 2008)
During high-speed end milling of aeronautical-grade aluminum alloy 7475-T7351 parts using tungsten carbide with cobalt binding (WC–Co) tools, unexpected chipping followed by catastrophic failure of the end mills was observed, while abrasive wear traces were absent. The tool breakage occurs usually with no warning and involves large portions of the tool tip. Broken tools presented extensive damage on all flutes. Results of the tests, finite element analysis (FEA) and scanning electron microscope (SEM) observations show that high temperatures generated during the cutting process activate the diffusion of aluminum into the tool material and formation of an eutectoid-containing cobalt aluminide (AlCo) with the cobalt used as binder. This hard and brittle eutectoid is compromising cobalt's role as binder between the carbide grains. The penetration of the aluminum in the tool material becomes deeper with the exposure time and temperature of the contact, until the whole tool tip becomes fragile and subject to chipping and further to heavy damage. The paper presents this unusual and not well known form of diffusion wear, which is preventing manufacturers to make full use of the tungsten carbide tools for high-speed machining of aeronautical aluminum.